2006
DOI: 10.1590/s0036-46652006000400006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological aspects of HTLV-II infection in São Paulo, Brazil: presence of Tropical Spastic Paraparesis/HTLV-Associated Myelopathy (TSP/HAM) simile diagnosis in HIV-1-co-infected subjects

Abstract: SUMMARYIn this study, the epidemiological and clinical features observed in solely HTLV-II-infected individuals were compared to those in patients co-infected with HIV-1. A total of 380 subjects attended at the HTLV Out-Patient Clinic in the Institute of Infectious Diseases "Emilio Ribas" (IIER), São Paulo, Brazil, were evaluated every 3-6 months for the last seven years by infectious disease specialists and neurologists. Using a testing algorithm that employs the enzyme immuno assay, Western Blot and polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…16 The relationship between HTLV-2 and neurological and systemic diseases is less well defined, although it appears that it is less frequent and less severe. [17][18][19][20] Syndromes that are part of the neurological complex related to HTLV-1 have a distinct pathogenic substrate from adult T-cell leukemia/lymphoma (ATL). 2 It is also not entirely clear how HTLV resists a competent immune system or what determines risk of development of the diseases associated with it.…”
Section: Transmissionmentioning
confidence: 99%
“…16 The relationship between HTLV-2 and neurological and systemic diseases is less well defined, although it appears that it is less frequent and less severe. [17][18][19][20] Syndromes that are part of the neurological complex related to HTLV-1 have a distinct pathogenic substrate from adult T-cell leukemia/lymphoma (ATL). 2 It is also not entirely clear how HTLV resists a competent immune system or what determines risk of development of the diseases associated with it.…”
Section: Transmissionmentioning
confidence: 99%
“…Besides the general population, a high percentage of intravenous drug users (IVD) from urban areas of Brazil, mostly HIV-1-infected, harbor HTLV-1/2 (Barbosa de Carvalho et al, 1996;Casseb et al, 1997a;Caterino-de-Araujo et al, 1998;de Araujo et al, 1994;Etzel et al, 2001;Gabbai et al, 1993;Moreira et al, 1993;Morimoto et al, 2005;Vallinoto et al, 1998). Several diseases, including adult T-cell leukemia (ATL), HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), other neurological syndromes, pneumonia, arthritis, bronchitis, and dermatological and urinary diseases, are associated with HTLV-1 and/or HTLV-2 infection in Brazil Macedo et al, 2004;Montanheiro et al, 2005;Pombo de Oliveira et al, 1995;Posada-Vergara et al, 2006). Accurate diagnosis of these viruses is therefore important to ensure prompt and appropriate care of infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-1 is the etiological agent of adult T cell leukemia/lymphoma and tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM), 1 and HTLV-2, although it is not associated with a certain disease, has been detected in patients with some neurological disorders, similar to TSP/HAM. [2][3][4] HIV is responsible for the AIDS world pandemic, and HIV/HTLV-1/2 coinfections have been associated with a delay or acceleration in the progression of cooccurring diseases. [5][6][7] In 2012, the UNAIDS reported that there were an estimated 35.3 (32.2-38.8) million infected individuals living with HIV worldwide, 8 and in Brazil, the Ministry of Health estimated that there were 686,478 AIDS cases from 1980 to June 2013.…”
mentioning
confidence: 99%